Bioinformatics and functional genomics - Pevsner, Jonathan, 1961- (Chichester : Wiley-Blackwell, 2015)
Bioinformatics and Functional Genomics provides a broad-based introduction to bioinformatics by following three real-world examples throughout the book: retinol-binding protein, breast cancer, and a calcium binding site C2. The author emphasizes the use of computational tools and databases to study connections between the structure of proteins and genes to function, development, evolution, and disease. Readers learn real skills, such as how to analyze genes and proteins, how to make trees using phylogenetic software, how to extract data, and how to identify genes and proteins implicated in diseases.
Keywords: Basic Sciences. Bioinformatics -- Bioinformatics (General).; Basic Sciences. Bioinformatics -- Proteomics; Bioinformatica